Simultaneous Acute Cholecystitis and Acute Appendicitis Treated by a Single Laparoscopic Operation - Jonas P. DeMuro (Case Reports in Surgery)
While acute appendicitis and acute cholecystitis are both common, they are only rarely seen simultaneously. The clinical presentation and hospital course of a 45-year-old female with concurrent acute appendicitis and acute cholecystitis is presented. The laparoscopic approach is ideal for dealing with multiple, simultaenous abdominal pathologies.